Social Funds : Assessing Effectiveness - Operations Evaluation Department (Washington, DC: World Bank, 2013)
This study is the first independent evaluation of social fund projects by OED. It reviews the development effectiveness of social fund projects and draws implications for future Bank support to them. It responds to the interest of the World Bank's Board of Executive Directors for an independent evaluation of this fast-expanding portfolio. The review is based on an examination of existing data and literature, and brings to bear new information relating to the participatory process in social fund projects and their institutional development impacts at the government, nongovernment, and community levels. The report finds that social fund projects have been highly effective in delivering small-scale infrastructure, but much less so in achieving consistently positive and significant improvements in outcomes and welfare impacts. While social fund projects have delivered slightly more than proportional benefits to the poor and the poorest, there have also been a significant number of non-poor beneficiaries. Most social fund beneficiaries are satisfied with the financed subprojects, but the greatest community problems have not necessarily been addressed and there is no assurance that the selected subprojects ensure the highest net benefits to the community.